Transcriptome-Wide Identification and Expression Profiling of the DOF Transcription Factor Gene Family in Chrysanthemum morifolium - Song, Aiping; Gao, Tianwei; Li, Peiling; Chen, Sumei; Guan, Zhiyong; Wu, Dan; Xin, Jingjing; Fan, Qingqing; Zhao, Kunkun; Chen, Fadi (Frontiers in Plant Science, 2016)
The family of DNA binding with one finger (DOF) transcription factors is plant specific, and these proteins contain a highly conserved domain (DOF domain) of 50-52 amino acids that includes a C2C2-type zinc finger motif at the N-terminus that is known to function in a number of plant processes. Here, we characterized 20 DOF genes in the important ornamental species chrysanthemum (Chrysanthemum morifolium) based on transcriptomic sequences. Phylogenetic analysis identified one pair of putative orthologous proteins in Arabidopsis and chrysanthemum and six pairs of paralogous proteins in chrysanthemum. Conserved motifs in the DOF proteins shared by Arabidopsis and chrysanthemum were analysed using MEME. Bioinformatics analysis revealed that 13 CmDOFs could be targeted by 16 miRNA families. Moreover, we used 5’ RLM-RACE to map the cleavage sites in CmDOF3, 15 and 21. The expression of these 20 genes in response to phytohormone treatments and abiotic stresses was characterized, and the expression patterns of six pairs of paralogous CmDOF genes were found to completely differ from one another, except for CmDOF6 and CmDOF7. This work will promote our research of the various functions of DOF gene family members in plant hormone and stress responses.